PKM KELOMPOK PEMBUAT KERUPUK RAMBAK DI DESA GESIKAN, GANTIWARNO, KLATEN, RANCANG BANGUN ALAT PENGADUK ADONAN DAN PENGIRIS SERTA PENERAPAN PRODUKSI BERSIH UNTUK MENINGKATKAN KAPASITAS PRODUKSI DAN KUALITAS LINGKUNGAN SEKITAR - Yuli Purwanto; Paramita Dwi Sukmawati; Maria Titah Jatipaningrum (LPPM IST AKPRIND Yogyakarta, 2019)
In the village of Bayanan, Gesikan Gantiwarno Klaten there is a home industry in the food sector. The home industry makes rambak crackers with two types, that is thin rambak and long rambak which is usually called “gilig”. The number of rambak business in Dusun Bayanan is 10 and to maintain the price and marketing of this micro business group has formed a communication container in the form of a cooperative called Koperasi Seroja Makmur. In the process of making rambak crackers, almost all do the production manually. For example, mixing the dough and cutting / slicing the dough is done by hand so that it causes the thin thickness of the rambak crackers to be different. Besides other problems that arise are waste generation in the production process, including waste in the form of used cooking oil, ash / charcoal residue from burning and smoke which can pollute the surrounding environme. So an effort should be made to minimize the waste produced. And also there is no control of the end result from the production of rambak crackers so that the quality of the product is not well maintained. Appropriate technology for kneading dough mixer and dough slicer is a solution for makers of rambak crackers because it can increase production yields and maintain quality. By providing insights and simple ways clean production of a product also becomes a program to maintain product quality and control the quality of product results.